Practice as research approaches to creative arts enquiry - Barrett, Estelle; Bolt, Barbara (London I. B. Tauris, 2010)
Practice-led research is a burgeoning area across the creative arts, with studio-based doctorates frequently favoured over traditional research. Yet until now there has been little published guidance for students embarking on such research. Designed specifically as a research training tool, the book is structured on the model used by most research programmes. A comprehensive introduction lays out the book's framework and individual chapters provide concrete examples of studio-based research in art, film and video, creative writing and dance, each contextualised by a theoretical essay and complete with references.
Originally published: 2007.
Includes bibliographical references (pages 169-179)
Keywords: Arts -- Research; Electronic books